YKWI (1952-2010): Sejarah Lima Puluh Delapan Tahun Pendidikan Perempuan di Pekanbaru - Wilaela Wilaela (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
Women’s education in Riau has a relationship with daughter diniyah long measdow under the auspices of the Foundation of Islamic Woen Union (YKWI). YKWI over 58 years to education for all in Pekanbaru successfully arranged. YKWI dynamics in the field of education of women and children in Pekanbaru can be characterized from the opening of schools, madrassas and places of course.